Academic Global Surgery: Creating Opportunities, Equity, and Diversity. Issue 1 (14th February 2023) - Vaghaiwalla, Tanaz; Gyawali, Sandesh; Jayaram, Anusha; Nathani, Priyansh; Sawhney, Riya; Long, Kristin; Dodgion, Christopher; Raykar, Nakul; Puyana, Juan Carlos; Joshi, Anip
A workforce trained in the development and delivery of equitable surgical care is critical in reducing the global burden of surgical disease. Academic global surgery aims to address the present inequities through collaborative partnerships that foster research, education, advocacy and training to support and increase the surgical capacity in settings with limited resources. Barriers include a deficiency of resources, personnel, equipment, and funding, a lack of communication, and geographical challenges. Multi–level partnerships remain fundamental; these types of partnerships include a wide range of trainees, professionals, institutions, and nations, yet care must be taken to avoid falling into the trap of surgical "voluntourism" and undermining the expertise and practice of long–standing frontline providers. Academic global surgery has the benefit of developing a community of surgeons who possess the tools needed to collaborate on individual, institutional, and international levels to address inequities in surgery that are spread variously across the globe. However, challenges for surgeons pursuing a career in global surgery include balancing clinical responsibilities while integrating global surgery as a career during training. This is due in part to the lack of mentorship, research time, grant funding, support to attend conferences, and a limitation of resources, all of which are significantly more pronounced for surgeons from low–resource countries.